Analysis of the Competitiveness of Indonesian Rubber Exports in International Markets - Anggi Radzma Fidhayanti; Nuriah Yuliati; Nisa Hafi Idhoh Fitriana (Westscience Press, 2024)
Indonesia's position as one of the largest rubber producing countries in the world does not make Indonesia a major rubber exporter on the international market. This research aims to analyze comparative competitiveness, competitive competitiveness and specialization of Indonesian rubber trade in the international market. The research methods used are Revealed Comparative Trade Advantage (RTCA), Export Competitiveness Index (XCi), and Trade Specialization Index (ISP). This research uses secondary data for the 2012-2021 period obtained from the Food and Agriculture Organization (FAO) and processed using Microsoft Excel tools. The research results show that Indonesian rubber commodities do not have comparative competitiveness, competitive competitiveness and trade specialization as a rubber importer in the international market. RCTA analysis shows an average value of -1.187 placing Indonesia in fourth position among other competing countries. XCi analysis shows an average value of 0.817 making Indonesia the country with the lowest competitiveness compared to other competing countries. ISP analysis shows that Indonesia tends to be a rubber importer with an average value of -0.573 and is at the import substitution stage.